PENGEMBANGAN KOMPETENSI PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN TAKALAR - Hamzah, Ilham; Burhanuddin, Burhanuddin; Wahid, Nur (Universitas Muhammadiyah Makassar, 2023)
This research is to find out how the form of competency development of civil servants in the Agency for Personnel and Human Resources Development Takalar Regency. This type of research is a qualitative descriptive research that is sourced from data using purposive sampling technique. and Human Resource Development for Takalar Regency. Data collection techniques used methods, namely, observation, interviews and documentation related to competency development of civil servants in the Personnel and Human Resources Development Agency of Takalar Regency. The results showed that the competency development of civil servants in the Agency for Personnel and Human Resources Development in Takalar Regency based on the results of research conducted by researchers was stated to be quite good. This is because it has met the indicators that can support the development of employee competencies seen from the indicators of Formal Education, Education and Training (Training), Courses, Upgrading, Seminars, Workshops and Workplace Traini